The VLT LBG redshift survey - VI. Mapping HI in the proximity of z ~ 3 LBGs with X-Shooter - Bielby, R.M. (2017)
We present an analysis of the spatial distribution and dynamics of neutral hydrogen gas around galaxies using new X-Shooter observations of z ~ 2.5-4 quasars. Adding the X-Shooter data to our existing data set of high-resolution quasar spectroscopy, we use a total sample of 29 quasars alongside ~1700 Lyman Break Galaxies (LBGs) in the redshift range 2 ≲ z ≲ 3.5. We measure the Lyα forest auto-correlation function, finding a clustering length of s0 = 0.081 ± 0.006 h-1 Mpc, and the cross-correlation function with LBGs, finding a crossclustering length of s0 = 0.27 ± 0.14 h-1 Mpc and power-law slope γ = 1.1 ± 0.2. Our results highlight the weakly clustered nature of neutral hydrogren systems in the Lyα forest. Building on this, we make a first analysis of the dependence of the clustering on absorber strength, finding a clear preference for stronger Lyα forest absorption features to be more strongly clustered around the galaxy population, suggesting that they trace on average higher mass haloes. Using the projected and 2-D cross-correlation functions, we constrain the dynamics of Lyα forest clouds around z ~ 3 galaxies. We find a significant detection of large-scale infall of neutral hydrogen, with a constraint on the Lyα forest infall parameter of βF = 1.02 ± 0.22.